Motywacje Rosjanek poszukujących muzułmańskiego męża. Próba rekonstrukcji postaw - Kończak, Izabela (Historia i Polityka, 2017)
The Russian Federation is a multiethnic and multi-faith state, where representatives of different nations and religions live close to one another. The natural proximity of so many nations can be the reason for the increase or decrease of ethnic distance. What is more, it may foster intercultural mixed marriages. The issue of popularity of marriages between Muslims and residents of Slavic Russia has been attracting the Russian public opinion for several years. The article discusses the motivations of Russian women, non-Muslims seeking a Muslim husband. The analysis is based on the quantitative and qualitative content of messages posted on the Internet portal Moya sem’ya to thread Vy lubite kavkaskikh/vostochnykh mushchin? The author took an attempt to answer the question why Muslims – usually coming from the North Caucasus – are – according to Russian women – better candidates for a life partner.